(untitled) (Nusantara Medical Science Journal, 2016)
ABSTRACT Introduction: It has been reported that obese children have a higher incidence of high ferritin and transferrin saturation than non obese children. The excessive iron stores can cause type 2 diabetes among patients with hemochromatosis, and this event could also occurred in obesity. Objectives: This study sought to know the level of serum ferritin and iron (ferrum) in adolescent obesity which could lead to initiate insulin resistance. Methods: Fifty five adolescence women (3 obese, 22 overweight, and 30 normal weight) involved in this study. The obesity was determined by body mass index (BMI), which are obese if BMI > 30 kg/m2; overweight if BMI 25-30 kg/m2; and normal weight if BMI < 25 kg/m2. The serum level of iron and ferritin assessed by kit analyzer with immunochemiluminescent methods, after drawing 2 ml blood from cubital vein. Conclusions: We concluded that serum ferritin and iron (ferrum) higher in obese group than overweight and normal weight group, although it was not statistically significance (Kruskall Wallis test p > 0.05). It was appeared that serum ferritin and iron tended to elevated following the raising of body mass index (BMI). Keywords : obesity, serum ferritin, serum iron (ferrum)